(untitled) (Third Sector Social Economic Review, 2022)
Welfare state has objectives such as ensuring income justice in a society, meeting the needs of citizens at a minimum level, increasing social participation and functionality especially among disadvantaged groups. The policies which are crucial in terms of achieving a certain standard of living for all individuals and ensuring social order, are implemented through the social budget. In this context, the budget allocated to social expenditures in a country is one of the key indicators of the effectiveness of the social state in that country. This study aims to examine the social budget allocation policies in the general budget in Turkey. For this purpose, a dynamic analysis of the social budget realizations in the budget policies implemented during the 2008-2020 period has been made. The data used in the study has been compiled from the official web pages of institutions such as the Ministry of Finance and the Turkish Statistical Institute (TUIK), Eurostat and OECD. Analyzing the data compiled from the official web pages of institutions such as the Ministry of Finance, Turkish Statistical Institute (TUIK), Eurostat and OECD, it has been seen that the largest share in social protection expenditures in Turkey is reserved for the retired/elderly field. For the period examined, the average of the GDP ratio of social protection expenditures in Turkiye was 12%, and it remained below the average of 27% of the European Union countries and 20% of the OECD countries.